Analisis Proses Hukum Yang Dapat Dijalani Oleh Content Creator Untuk Menegakkan Hak Orisinalitas - Pandito Malim Hasayangan Tanjung; Zalzabila Agnia Husna (Lembaga Pengembangan Kinerja Dosen, 2024)
In the turbulent digital era, originality rights have become a crucial issue for content creators. This article analyzes the legal process that content creators can undergo to enforce their originality rights. The first step in this process is proving copyright ownership, which involves gathering strong evidence of the original ownership of the work. After that, content creators can apply for a cease and desist order against the infringing party, as a preventive measure before entering the judicial stage. If the injunction is ineffective, the content creator can take further legal steps by filing a civil suit in court. In addition, content creators can also utilize alternative dispute resolution such as mediation or arbitration. Cross-border cooperation and international agreements are also important in the protection of originality rights at a global level. Understanding these legal processes is important for content creators to ensure that their works are respected and protected in the ever-evolving digital environment.